Historiciser les langues en classe de français langue étrangère à travers des démarches de croisement de récits - Hara Papasαϊκα (Recherches en didactique des langues et des cultures)
The didactic approaches designed and presented in this article place the historicity of language comprehension and production at the heart of teaching/learning French as a Foreign Language. On the one hand, they aim to highlight that comprehension, especially in one’s first language, emerges from perceptions steeped in history, either in the narrower sense of disciplinary knowledge or in the broader sense of collective and memorial experience. On the other hand, their objective is to help students realize that language productions are historically situated processes, meaning they are constructed from diverse perspectives. Suggesting historical documents in a foreign language classroom, such as an audiovisual document in French about the Ottomans and the devshirme system established by them, and thereby exposing students to an otherness perspective, would allow them to question preconceived meanings, potentially transforming them and embracing the diversity of worldviews. Ultimately, this process would lead to a transformation of the students themselves through different language prisms.historicity, historicization, language teaching